Teacher’s collaboration and perception of assessment while co-planning a conversation course: A Paraná Speaks English Experience - Andrade, Lucas Ricci Pereira de; Ortenzi, Denise Ismênia Bossa Grassano (The ESPecialist, 2025)
Growing globalization has increased connections between people and institutions across the globe. In this context, the internationalization of higher education is a relevant demand from this new global order. To support this process, state initiatives are created to enhance internationalization, and in Paraná state, the program Paraná Speaks English is one of them (SENEFONTE, 2021). Consequently, forming pre-service teachers to act in this context is an issue to be explored. The study investigated the formative potential of the collaborative work of PFI in the training of a pre-service teacher regarding assessment concepts. This work is situated in a social-cultural perspective, arguing that human development is a consequence of social interaction, focusing on the cognitive development that emerged through co-planning assessments for a mini-course. The data source is messages from a group chat on a virtual messenger, where most of the co-planning happened. To analyze this data, we use Activity Theory (ENGESTRÖM, 1987), concept formation (VYGOTSKY, 1978), and concepts of assessment (SCARAMUCCI, 2006; FURTOSO, 2008; HAYDT, 2004; CRISP, 2012; BIGGS, 1996). Results showed that different assessment concepts appeared and were created throughout the co-planning of this mini-course. It is also possible to conclude that the collaborative aspect shown in this activity was positive for the cognitive development of teachers. This paper can indicate Paraná Speaks English as a possible context for training pre-service teachers for the internationalization context.